Stratégies argumentatives du genre cyber-epistolaire : rhétorique de l’arnaque et (en)jeux de faces - Zacharie Hatolong Boho; Romuald Valentin Nkouda Sopgui (Multilinguales)
Thanks to the spectacular development of ICT and the vulgarization of Internet, there is a growing cyber-epistolary genre whose expeditors, difficult to identify because of their virtual status, use as a scam weapon. The analyzed corpus is constituted of spammed emails by virtue of both their doubtful origin and cybercriminal aspect. Accordingly, several linguistic and stylistic processes are used, such as familiarity/intimacy tactics and positive expressions, which clear up rapidly surprise and suspicion that recipients might naturally demonstrate. We will show that if some of these processes are based on the message texture, others tend to focus on referents, with an emphasis on the representative function of language.